2020
DOI: 10.1038/s41598-019-57230-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of clinical phenotype and prognosis of hypertrophic cardiomyopathy complicated with hypertension

Abstract: We here studied the clinical features, cardiac structure, and functional changes and prognosis of hypertrophic cardiomyopathy (HCM) patients with hypertension (HTN). A total of 90 HCM patients with HTN and 172 patients without HTN were divided into a hypertensive group and non-hypertensive group. the clinical characteristics, cardiac structure and function, and prognosis of the two groups were compared. our study found that HcM patients with Htn had fewer syncope events in their medical histories (8% vs. 22%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Consistent with previous studies ( Luo et al, 2020 ; Deng et al, 2019 ; Aslam et al, 2010 ), the clinical features of HCM patients with hypertension in the present study were characterized by older age, higher application of other antihypertensive drugs except β blockers, such as renin-angiotensin system inhibitors (RASIs), dihydropyridine calcium channel antagonists (DHP-CCBs) and hydrochlorothiazide. Vasodilators were the most effective and tolerable drugs for blood pressure control but could exacerbate LVOTO.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies ( Luo et al, 2020 ; Deng et al, 2019 ; Aslam et al, 2010 ), the clinical features of HCM patients with hypertension in the present study were characterized by older age, higher application of other antihypertensive drugs except β blockers, such as renin-angiotensin system inhibitors (RASIs), dihydropyridine calcium channel antagonists (DHP-CCBs) and hydrochlorothiazide. Vasodilators were the most effective and tolerable drugs for blood pressure control but could exacerbate LVOTO.…”
Section: Discussionsupporting
confidence: 91%
“…Vasodilators were the most effective and tolerable drugs for blood pressure control but could exacerbate LVOTO. Historical studies indicated that the presence of LVOTO did not differ between HCM patients with hypertension or those without hypertension ( Luo et al, 2020 ; Aslam et al, 2010 ). While the prevalence of LVOTO was much higher in the hypertension group of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comorbidity influencing hemodynamics should be considered in outcome prediction. 66 , 67 , 68 , 69 , 70 …”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Procollagen type I carboxy‐terminal propeptide and matrix metalloproteinase‐2 levels in both plasma and myocardial tissues were consistent, reflecting myocardial fibrosis. Furthermore, comorbidity influencing hemodynamics should be considered in outcome prediction 66–70 …”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%